Systematic review and meta-analysis on prevalence and antimicrobial resistance patterns of important foodborne pathogens isolated from retail chicken meat and associated environments in India - Ayoub, H.; Kumar, M.S.; Dubal, Z.B.; Bhilegaonkar, K.N.; Hung Nguyen-Viet; Grace, Delia; Thapliyal, S.; Sanjumon, E.S.; Sneha, E.N.P.; Premkumar, D.; Rajendran, V.K.O.; Deka, Ram Pratim (MDPI, 2025)
The chicken value chain, a vital part of the global food supply, also represents a significant public health concern due to the risk of foodborne pathogens, particularly in low- and middle-income countries (LMICs) such as India. This systematic review and meta-analysis aimed to assess the prevalence of significant bacterial pathogens including Salmonella spp., Campylobacter spp., Escherichia coli, Staphylococcus aureus, Listeria monocytogenes, Clostridium perfringens, and Klebsiella pneumoniae. in retail chicken meat and associated environments and the antimicrobial resistance based on the articles published between January 2010–December 2023. The research adhered to the guidelines in the ’Preferred Reporting Items for Systematic Review and Meta-Analysis’ (PRISMA). Based on 90 included studies, S. aureus showed the highest pooled prevalence (56%; 95% CI: 38–74%), followed by E. coli (50%; 95% CI: 37–64%), C. perfringens (35%; 95% CI: 10–65%), and K. pneumoniae (21%; 95% CI: 7–38%). Salmonella spp. (95% CI: 11–26%) and Campylobacter spp. (95% CI: 11–27%) exhibited similar prevalence rates at 18%, while L. monocytogenes had the lowest prevalence at 13% (95% CI: 1–33%). A sensitivity analysis was subsequently conducted to assess the impact of influential studies, and the pooled prevalence of each pathogen was recalculated after removing these studies to ensure the robustness of the results. The pathogens, specifically Salmonella spp. and Campylobacter spp., displayed high levels of resistance to medically important antimicrobials (erythromycin, tetracycline, ciprofloxacin, colistin), a potential threat to human health. This study advocates for a collaborative and comprehensive approach, reflecting the multifaceted nature of the issue, and highlighting the importance of a holistic strategy to safeguard public health and maintain antibiotic effectiveness in the face of emerging challenges.